2017
DOI: 10.1155/2017/1421326
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Cognitive Impairment through the Looking Glass of Transcranial Magnetic Stimulation

Abstract: In the last years, there has been a significant growth in the literature exploiting transcranial magnetic stimulation (TMS) with the aim at gaining further insights into the electrophysiological and neurochemical basis underlying vascular cognitive impairment (VCI). Overall, TMS points at enhanced brain cortical excitability and synaptic plasticity in VCI, especially in patients with overt dementia, and neurophysiological changes seem to correlate with disease process and progress. These findings have been int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 117 publications
(159 reference statements)
4
38
0
Order By: Relevance
“…We should acknowledge that calcium-channel agonists consistently increase ICF [30]; nonetheless, the assumption of a top-down regulation of ICF induced by the NE brain concentration is speculative at the moment. Furthermore, previous TMS studies carried out in a clinical context highlighted the electrophysiological role of ICF changes as potential markers of a glutamate-mediated adaptive response or compensatory neuroplastic phenomena [42,43,44,45,46,47]. Thus, we cannot rule out an indirect (adaptive) modulatory effect on ICF.…”
Section: Discussionmentioning
confidence: 83%
“…We should acknowledge that calcium-channel agonists consistently increase ICF [30]; nonetheless, the assumption of a top-down regulation of ICF induced by the NE brain concentration is speculative at the moment. Furthermore, previous TMS studies carried out in a clinical context highlighted the electrophysiological role of ICF changes as potential markers of a glutamate-mediated adaptive response or compensatory neuroplastic phenomena [42,43,44,45,46,47]. Thus, we cannot rule out an indirect (adaptive) modulatory effect on ICF.…”
Section: Discussionmentioning
confidence: 83%
“…Several studies, although methodologically heterogeneous and most of them open-label in design, have shown that specific paradigms of stimulation might improve cognitive performance, thus possibly becoming an alternative to conventional neuroleptic therapy for psychiatric symptoms of dementia [79]. In AD, these effects are probably mediated by compensatory mechanisms supporting the residual abilities [80], and the efficacy can be maximized by selecting patients on the basis of putative neurophysiological markers [78].…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the normality of CSP and SICI in VD patients indicates that the mechanisms regulating GABAergic intracortical inhibitory circuits are not involved in these individuals. These data provide a new and intriguing neurophysiological explanation for the differences in the neurobiological processes that underlie nonvascular early onset major depression and late-onset VD (Bella et al., 2011; Concerto et al., 2013; Lanza et al., 2017). Furthermore, a longitudinal study evaluated the electrophysiological changes and progression of cognitive decline in patients with subcortical cerebrovascular lesions, and the results showed that glutamate-related neuroplasticity was differentially enhanced between patients with and without VD.…”
Section: Tms In Depressionmentioning
confidence: 99%
“…These symptoms may even present in the preclinical or early stages of these diseases (Bella et al., 2011a, 2011b, 2013; Lanza et al., 2013; Pennisi et al., 2016; Lanza et al., 2017). …”
Section: Introductionmentioning
confidence: 99%